Export Specialisation of Bulgaria in the Relations with the European Union (1999-2007) - Zhelev, Paskal (Research Papers, 2009)
The paper is an attempt to analyze and asses the export specialisation of Bulgaria and its place in the intra-community division of labour in the European Union. Given the high openness of theBulgarian economy towards the EU, the quality and dynamics of its export specialisation vis-a-vis the EU predetermine to a great extent the national economy structural changes, its growth rates and the well-being of the population.Though most of the analyzed indicators for export structure, comparative advantages, factor intensity, technological competitiveness, degree of processing and value added of exports, intensity of intra-industry specialisation show a favorable trend of improvement in recent years, in comparative perspective it is concluded that Bulgaria has developed a relatively unfavorable, low-grade and not perspective international specialisation in the relations with the EU. During the analyzed period (1999-2007) Bulgaria has objectively taken up a position of a peripheral economy, substantially differing in structural and technological aspect not only from the old member states but also from the newly acceded ones.This calls for implementation of a purposeful, large-scale, realistic national strategy for promoting the Bulgarian economy competitiveness and improvement of its place in the intracommunity division of labour.